2011
DOI: 10.1016/j.vetmic.2011.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Airborne transmission of a highly pathogenic avian influenza virus strain H5N1 between groups of chickens quantified in an experimental setting

Abstract: Airborne transmission of a highly pathogenic avian influenza virus strain H5N1 between groups of chickens quantified in an experimental setting. Veterinary Microbiology, Elsevier, 2011, 152 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…There have been few studies on aerosol transmission of influenza A virus, and were reviewed by Tellier (2009). In brief, these studies have shown that the rate of airborne transmission is both low and inefficient, even over short distances (Tsukamoto et al 2007;Spekreijse et al 2011;Gustin et al 2011).…”
Section: Vector Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…There have been few studies on aerosol transmission of influenza A virus, and were reviewed by Tellier (2009). In brief, these studies have shown that the rate of airborne transmission is both low and inefficient, even over short distances (Tsukamoto et al 2007;Spekreijse et al 2011;Gustin et al 2011).…”
Section: Vector Mediamentioning
confidence: 99%
“…Therefore, workers in industrial food animal production systems may inadvertently act as a 'bridge' for viruses between animal and human populations. A recent study has shown that the amount of dust produced by large poultry flocks may be high, and that dust-borne infection may be facilitated via artificial ventilation (Spekreijse et al 2011).…”
Section: Commercial Systemmentioning
confidence: 99%
“…Studying dust‐borne virus spread of HPAIv during a disease‐free period is difficult, and the only way of gaining insight into distance‐related spread is by doing experiments. In a previous study, the rate of airborne transmission of HPAIv over short distances (up to 1·2 m) within an experimental unit was determined, and it was demonstrated that virus could be transmitted over a short distance and that dust was the possible vector of transmission 26 . A study by Yee et al.…”
Section: Introductionmentioning
confidence: 99%
“…As the relative contribution of different transmission mechanisms is poorly understood (Spekreijse et al, 2011a), the total infection pressure, β , was modelled as the sum of the infection pressure due to two independent routes; namely transmission via: (i) aerosol ( β a ), which represented direct bird-to-bird contact (i.e. dependent on ‘ I ’); and (ii) via infectious faeces ( β f ), which represented indirect contact via faecal contamination of dust and drinking/feeding equipment (i.e.…”
Section: Methodsmentioning
confidence: 99%